Resources and activities of dermatovenereological medical organizations in Russian Federation in 2013 - A. A. Kubanova; L. E. Melekhina; A. A. Kubanov; E. V. Bogdanova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article provides analysis of dermatovenereological medical organizations resources and activities and overview of incidence of sexually transmitted infections and skin disorders in Russian Federation in 2013.